Association between social capital and depression among older adults of different genders: Evidence from Hangzhou, China - Zhou, Siyu; Li, Kai; Ogihara, Atsushi; Wang, Xiaohe (Frontiers in Public Health, 2022)
With the increase in life expectancy and the impact of the “one-child” family planning policy in China, coping with depression in older adults has become an important issue. This study determines and explore the association between social capital and depression among older adults of different genders, analyzes the influence of social capital on depression. A total of 1,042 participants were selected from four areas that included personal information from electronic health records. Social capital measurements and GDS-15 scale were used to calculate social capital and depression. Multivariate logistic regression and structural equation modeling were used to examine the associations between social capital and depression among older adults of different genders. This study showed lower reciprocity (male, female), social work (male), and trust (female) indicated a higher risk of depression. Reciprocity and social network were significantly negatively correlated with depression in the male group. Trust, reciprocity, and social participation have a positive effect on reducing depression risk, but social networks have a negative effect on depression in the male model. In contrast to the male model, social networks and social participation have a negative effect on depression in the female model. This finding indicates a significant gender difference in the effect of social capital on depression and older adults can reduce depression risk by increasing social capital.